Comorbidity Burden in Trial-Aligned Patients with Established Gout in Germany, UK, US, and France: a Retrospective Analysis. Issue 7 (July 2016) - Nyberg, Fredrik; Horne, Laura; Morlock, Robert; Nuevo, Javier; Storgard, Chris; Aiyer, Lalitha; Hines, Dionne; Ansolabehere, Xavier; Chevalier, Pierre
Abstract Introduction Patients with gout have numerous comorbidities. We aimed to estimate the prevalence and incidence rates of renal and cardiovascular morbidities in trial-aligned patients with established gout in Germany (DE), the United Kingdom (UK), the United States (US), and France (FR). Methods This longitudinal cohort study used retrospective data from IMS Disease Analyzer™ (DE, FR), Clinical Practice Research Datalink–Hospital Episode Statistics (UK), and IMS' PharMetrics Plus database linked with outpatient laboratory results (US). Included patients were ≥18 years at index date (January 1, 2010; all dates +1 year for FR), with continuous enrollment during the pre-index year, had "prevalent established gout" determined by data in the pre-index year, and ≥1 documented visit after index date; additional inclusion/exclusion criteria were aligned with recent gout clinical trials. Look-back for comorbidity prevalence extended to January 1, 2003 (US: January 1, 2009). Follow-up for incidence extended from index date to at most March 26, 2013 (FR: May 31, 2014). Events of interest were identified by diagnostic codes and/or laboratory data. Results The trial-aligned cohorts included 35, 118 (DE), 24, 607 (UK), 121, 591 (US), and 17, 338 (FR) patients. Among renal conditions, baseline diagnosis of chronic kidney disease/renal failure was most prevalent in the UK followed by DE; abnormal serum creatinine was most prevalent in the UK. Hypertension was the most prevalent cardiovascular diagnosis in all countries, followed by ischemic heart disease (IHD) and myocardial infarction. Incidence rates (per 100 patient-years) for new/worsening renal impairment ranged from 1.67 (DE) to 4.34 (US) and for nephrolithiasis diagnosis from 0.31 (FR) to 3.79 (US). The incidence rates for hypertension diagnosis were highest among cardiovascular-related events, ranging from 3.23 (UK) to 20.27 (US), followed by IHD. Conclusions Patients with established gout such as those included in gout trials have a high burden of established morbidity and new diagnoses of morbid events. Consideration of comorbidities, which greatly exacerbate disease burden, is important in gout management. Funding AstraZeneca.